Characterization of vibration and noise pollution of SI engine fueled with magnetized ethanol–gasoline blends by time–frequency methods. (December 2021) - Faraji, Hosna; Heidarbeigi, Kobra; Samadi, Sadegh
The purpose of the present study was to investigate the effects of magnetized ethanol–gasoline fuel blends on the vibration and sound status of a single-cylinder gasoline engine. Totally 36 tests were conducted including two factors: ethanol (blended by gasoline with share of 0, 5, 10, and 20%) and magnetic field intensity (0, 5300, and 7000 G) at three replications as a factorial experiment based on completely randomized design. The sound signals of the engine at 10 cm distance from the driver's ear were recorded and its engine vibration was measured in Z direction. The results of statistical analysis of vibration and sound data showed significant effects of both factors on the vibration and sound signals. The maximum sound pressure level with averages of 88.41 belonged to pure gasoline and magnetic intensity of 7000 G and minimum value (78.94 dB) belonged to 10% ethanol in the blended fuel and magnetic intensity of 5300 G. The driver can operate the engine for 10–20% ethanol shares with all studied magnetic intensities without use of any ear protector. In the presence of magnetic field, vibration decreased by increasing ethanol up to 10%. The maximum amount of vibration in frequency domain obtained without using magnetic field. For 5300 G magnetic intensity, the least amount of vibration was observed for all frequencies.